Analysis of Implementation of the Livestock Control Policy - Widodo Widodo; Agus Prastyawan; Pardamean Daulay (International Journal of Islamic Business and Management Review, 2025)
This research is a qualitative descriptive study that aims to analyze the implementation of the Mukomuko Regency Regulation No. 9 of 2019 concerning Livestock Control and obtain an overview of the factors that support and hinder the implementation of the policy using the Edward III model framework (1984). The variables studied consist of communication, resources, disposition and bureaucratic structure. Data collection was carried out using observation methods, in-depth interviews and documentation. Data sources or key informants consist of the Head of Mukomuko City Sub-district, Satpol PP, Head of BMA (Customary Consultative Body), livestock owners, and the Mukomuko City Sub-district Community. Analysis uses the interactive model of Miles and Huberman (1992) and triangulation of sources and methods. This study found that communication factors regarding livestock control policies in Mukomuko District were relatively minimal. Policy dissemination tended to be formal and limited, leaving most livestock owners unaware of the livestock control policies, resulting in minimal understanding, awareness, and compliance with these policies. The lack of resource support, including the number of implementers, their competence, facilities, budget, and incentives, coupled with the implementers' failure to implement sanctions and enforce the law effectively, led to a tendency for the community to ignore the regulations, indicating a low commitment from implementers to implement the policies. Public misunderstanding of the policy, minimal socialization, limited support for resources, budget, facilities and incentives, weak commitment and minimal bureaucratic coordination coupled with public views on the culture of livestock management that impacts economic losses, security, and order further exacerbate the obstacles faced in the implementation of livestock control policies in Mukomuko District, Mukomuko Regency. Therefore, in order to ensure effective implementation, communication innovation and budget support, facilities and incentives as well as community involvement are needed.